Synergistic actions of hematopoietic and mesenchymal stem/progenitor cells in vascularizing bioengineered tissues. - Eduardo K Moioli (Public Library of Science (PLoS), 2008)
Poor angiogenesis is a major road block for tissue repair. The regeneration of virtually all tissues is limited by angiogenesis, given the diffusion of nutrients, oxygen, and waste products is limited to a few hundred micrometers. We postulated that co-transplantation of hematopoietic and mesenchymal stem/progenitor cells improves angiogenesis of tissue repair and hence the outcome of regeneration. In this study, we tested this hypothesis by using bone as a model whose regeneration is impaired unless it is vascularized. Hematopoietic stem/progenitor cells (HSCs) and mesenchymal stem/progenitor cells (MSCs) were isolated from each of three healthy human bone marrow samples and reconstituted in a porous scaffold. MSCs were seeded in micropores of 3D calcium phosphate (CP) scaffolds, followed by infusion of gel-suspended CD34(+) hematopoietic cells. Co-transplantation of CD34(+) HSCs and CD34(-) MSCs in microporous CP scaffolds subcutaneously in the dorsum of immunocompromised mice yielded vascularized tissue. The average vascular number of co-transplanted CD34(+) and MSC scaffolds was substantially greater than MSC transplantation alone. Human osteocalcin was expressed in the micropores of CP scaffolds and was significantly increased upon co-transplantation of MSCs and CD34(+) cells. Human nuclear staining revealed the engraftment of transplanted human cells in vascular endothelium upon co-transplantation of MSCs and CD34(+) cells. Based on additional in vitro results of endothelial differentiation of CD34(+) cells by vascular endothelial growth factor (VEGF), we adsorbed VEGF with co-transplanted CD34(+) and MSCs in the microporous CP scaffolds in vivo, and discovered that vascular number and diameter further increased, likely owing to the promotion of endothelial differentiation of CD34(+) cells by VEGF. Together, co-transplantation of hematopoietic and mesenchymal stem/progenitor cells may improve the regeneration of vascular dependent tissues such as bone, adipose, muscle and dermal grafts, and may have implications in the regeneration of internal organs.